Interaction between Librarians' ICT Skills and Faculty Members’ Satisfaction with Information Delivery in University Libraries - Nnadozie , Chuma O. (MiddleBelt Journal of Library and Information Science, 2016)
The purpose of this paper was to find out the influence of Information and Communication Technology (ICT) skills of academic librarians on faculty members’ satisfaction with information services in university libraries in South-East Zone of Nigeria. The population of this study was made up of 112 librarians and 4469 lecturers drawn from eleven (11) out of nineteen (19) universities within the study area. The research design used was a combination of descriptive survey and linear correlation. Two (2) customized rating scales were used for data collection. Census sampling was applied in choosing librarians while stratified random sampling technique was used to select respondents from the lecturers’ sub-stratum. Out of the 447 and 112 copies of research instrument administered, 87 and 366 copies were returned by librarians and lecturers, respectively giving a total return-rate of 81.0%. Data was analyzed using a combination of descriptive and inferential statistics. The Pearson Product Moment Correlation (PPMC) was used to ascertain the strength of the relationship between ICT skills and faculty members' satisfaction (independent and dependent variables, respectively). Results from the correlation coefficient of the two variables showed that there is a weak and positive relationship between academic librarians’ ICT skills and the satisfaction derived by faculty members from services received in the sampled university libraries. Recommendations made include: provision of regular ICT literacy training for librarians, employment of competent ICT technicians/experts, adequate funding and automation of library services in the studied Nigerian university libraries.